Mr brown can moo1 can you ? - Seuss (London HarperCollins Children's Books, 2018)
Moo moo! Hoo hoo! Cock-a-doodle-doo! Oh, the wonderful sounds Mr. Brown can do. Now see if you can do them too! This fabulous book is ideal for teaching young children all about noises!